2004
DOI: 10.1124/dmd.104.001925
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION OF AFLOQUALONE N-GLUCURONIDATION: SPECIES DIFFERENCES AND IDENTIFICATION OF HUMAN UDP-GLUCURONOSYLTRANSFERASE ISOFORM(S)

Abstract: ABSTRACT:Afloqualone (AFQ) is one of the centrally acting muscle relaxants. AFQ N-glucuronide is the most abundant metabolite in human urine when administered orally, whereas it was not detected in the urine when administered to rats, dogs, and monkeys. Species differences in AFQ N-glucuronidation were investigated with liver microsomes obtained from humans and experimental animals. The kinetics of AFQ N-glucuronidation in human liver microsomes showed a typical Michaelis-Menten plot. The K m and V max values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The metabolic pathway of imidafenacin for N-glucuronidation, however, was uncommon in rats and dogs, and rats have the unique metabolic pathway for the oxidation on the phenyl moiety, generating M-8 and its related metabolites (Sato et al, unpublished observations). Species differences for N-glucuronidation were also observed in afloqualone in common with imidafenacin, indicating high N-glucuronidation activity in humans compared with activity in experimental animals except rabbits (Green and Tephly, 1998;Kaji and Kume, 2005).…”
Section: Position Of Carbonmentioning
confidence: 99%
“…The metabolic pathway of imidafenacin for N-glucuronidation, however, was uncommon in rats and dogs, and rats have the unique metabolic pathway for the oxidation on the phenyl moiety, generating M-8 and its related metabolites (Sato et al, unpublished observations). Species differences for N-glucuronidation were also observed in afloqualone in common with imidafenacin, indicating high N-glucuronidation activity in humans compared with activity in experimental animals except rabbits (Green and Tephly, 1998;Kaji and Kume, 2005).…”
Section: Position Of Carbonmentioning
confidence: 99%
“…UGT2B7 shows extreme regioselectivity in favoring M1 formation. Although the regioselectivity of glucuronidation for many endogenous and exogenous compounds (Kaji and Kume, 2005a;Bowalgaha et al, 2007;Kaivosaari et al, 2008) has been reported, the underlying mechanism is still difficult to address because the crystal structures of UGTs are largely unknown (Miley et al, 2007). The CL int (M1 ϩ M2) of UGT1A9 was approximately 8-fold higher than that in the UGT2B7 system, suggesting the predominant contribution from UGT1A9 in catalyzing the reduced TSA glucuronidation.…”
Section: Regioselective and Species-dependent Glucuronidation Of Tsamentioning
confidence: 99%
“…Species differences in the glucuronidation of Beviramat, an anti-HIV drug candidate, have been demonstrated in human, rat, mouse, dog and marmoset liver microsomes 24 . Species differences between human, rats, dogs and monkeys in the N-glucuronidation of the muscle relaxant Afloqualone were described by Kaji and Kume 40 . Some studies have demonstrated that cats have remarkably low hepatic levels of UGT1A6.…”
Section: Interspecies Differences In Ugt Enzymesmentioning
confidence: 99%